Volume Overload Initiates an Immune Response in the Right Ventricle at the Neonatal Stage - Cui, Qing; Sun, Sijuan; Zhu, Hongbin; Xiao, Yingying; Jiang, Chuan; Zhang, Hao; Liu, Jinfen; Ye, Lincai; Shen, Jie (Frontiers in Cardiovascular Medicine, 2021)
Background: Pulmonary regurgitation caused by the correction or palliation of pediatric tetralogy of Fallot (TOF) leads to chronic right ventricular (RV) volume overload (VO), which induces adolescent RV dysfunction. A better understanding of the molecular mechanism by which VO initiates neonatal RV remodeling may bring new insights into the post-surgical management of pediatric TOF. Methods and Results: We created a fistula between the abdominal aorta and inferior vena cava on postnatal day 1 (P1) using a rat model to induce neonatal VO. Echocardiography revealed that the velocity and velocity- time-integral of the pulmonary artery (PA) were significantly elevated, and hematoxylin and eosin (H&E) staining showed that the diameter of the RV significantly increased. RNA-seq analysis of the RV on P7 indicated that the top 10 enriched Gene Ontology (GO) terms and the top 20 enriched terms in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were associated with immune responses. Flow-cytometric analysis demonstrated that the number of CD4+and CD8+ immune cells were significantly augmented in the VO group compared with the sham group. Conclusions: A neonatal cardiac VO rat model on P1 was successfully created, providing a platform for studying the molecular biology of neonatal RV under the influence of VO. VO - induces an immune response at the neonatal stage (from P1 to P7), suggesting that immune responses may be an initiating factor for neonatal RV remodeling under the influence of VO and that immunosuppressants may be used to prevent pediatric RV remodeling caused by VO.